Analisis Faktor-Faktor yang Mempengaruhi Pelaksanaan Discharge Planning di Ruang Rawat Inap Rumah Sakit TK. II Udayana dan Rumah Sakit Bhayangkara Denpasar - Wiradani Ni Luh Kade; Diwyami Ni Putu (PrimA: Jurnal Ilmiah Ilmu Kesehatan, 2024)
Introduction: Discharge planning is a systematic process that is carried out from the beginning of the patient entering the hospital to prepare the patient to be able to move from hospital to home safely by health workers. The implementation of discharge planning that is structured and adapted to individual patients can reduce the length of hospital stay and the rate of re-hospitalization. Several studies in hospitals found that the implementation of discharge planning is still not optimal. Purpuse: The purpose of this study was to determine the factors that influence the implementation of discharge planning. Methods: This research was a descriptive-analytic study with a cross-sectional approach. The research sample was 124 nurses in the inpatient room. The sampling technique applied was total sampling. Data were collected using a questionnaire and analyzed by bivariate and multivariate. Result: The results of the bivariate analysis of all factors (personnel, involvement and participation, communication, time, agreement and consensus) had a significant influence on the discharge planning implementation (p<0.05). While the multivariate analysis showed that the time factor had the most dominant influence on the discharge planning implementation (p<0.001; AOR: 13.079; 95% CI: 3.724 – 45.928). Conclusion: Implementation of discharge planning is largely determined by the availability of time owned by nurses from planning to the evaluation of discharge planning. Suggestions: It is hoped that nurses in hospitals will spend more time on discharge planning optimally, so they can help to heal and to prevent patient disease recurrence.